2020
DOI: 10.3390/su12145872
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Higher Education: The Relationship between Work-Life Balance and XR E-Learning Facilities

Abstract: Nowadays, collaborative learning is proving to offer solutions to new inclusivity research challenges, and most importantly, can help ensure sustainable education. Collaborative learning can strengthen positive attitudes towards learning, improve performance in academic results, and enhance self-esteem, by promoting interaction and mutual support among young people. Extended reality (XR), associated with collaborative learning, offers a further advantage by facilitating deep comprehensive learning. An online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…University students seemed to be still capable of finding some gratification from the university context. They also need to be a catalyst for necessary changes in the society, so that their graduates can be part of the transformation of society in the direction of sustainable development [72]. Based on our correlational results and, as demonstrated in previous studies [56,63,73], academic efficacy beliefs, satisfaction and university sense of belonging could be considered as some relevant protective factors for students' mental health, suggesting that supportive university environments foster student flourishing.…”
Section: Discussionsupporting
confidence: 71%
“…University students seemed to be still capable of finding some gratification from the university context. They also need to be a catalyst for necessary changes in the society, so that their graduates can be part of the transformation of society in the direction of sustainable development [72]. Based on our correlational results and, as demonstrated in previous studies [56,63,73], academic efficacy beliefs, satisfaction and university sense of belonging could be considered as some relevant protective factors for students' mental health, suggesting that supportive university environments foster student flourishing.…”
Section: Discussionsupporting
confidence: 71%
“…An advanced m-learning technique is an augmented reality (AR). This technique shows digital information on images captured by a mobile device [36]. AR allows the display of stored data and 3D images, making any educational environment interactive and innovative.…”
Section: Use Of Mobile Devices In Educationmentioning
confidence: 99%
“…Anderson and Gerbing (1988) stated that the following two steps must be completed for a measured model: (1) under the consideration of the overall model, it is necessary to verify whether each measured variable in the model can accurately measure its latent variable; and (2) a test must be conducted to check whether there are complex measured variables with different latent variants under a load, in which both the convergent validity and discriminant validity must meet the standard. Based on the suggestions of Bagozzi and Yi (1988), this study selected the two most commonly-used pointers to evaluate the measured model, which are described as follows [85,86]:…”
Section: Measured Model Analysismentioning
confidence: 99%
“…They found that the immersive experience of students has a significant impact on their culture, living standards, and learning. In Austria, the University of Graz built an academic center for teacher-student interaction, based on a new teaching method that combines the interdisciplinary collaboration of STEAM (Science, Technology, Engineering, Art, and Mathematics) education and ESD [1]. Velázquez (2018) mentioned that the integration of augmented reality (AR) technology in the classroom can improve the students' motivation to learn, and that AR technology is systematic and procedural.…”
Section: Introductionmentioning
confidence: 99%